Advanced Magnetic Resonance Imaging for Detection of Liver Fibrosis and Inflammation in Autoimmune Hepatitis: A State-of-the-Art Review. - Gomes, Natália B.N.; Torres, Ulysses S.; Ferraz, Maria Lucia C.G.; D'Ippolito, Giuseppe (Seminars in Ultrasound, CT & MRI, 2024)
Autoimmune hepatitis is a rare chronic liver disease, associated with a high level of morbidity and high mortality; approximately 40% of patients with severe untreated disease die within 6 months of diagnosis. It should be treated to achieve complete biochemical and histologic resolution of the disease using corticosteroids and immunosuppression to prevent further progression to cirrhosis. The use of invasive liver biopsy is recommended for the staging and assessment of inflammation and fibrosis for treatment decision-making in the face of an unsatisfactory response or clinical remission, including being a determinant for withdrawal of immunosuppression. On the other hand, liver biopsy is invasive, costly, and not free of complications. It also has potential sampling error and poor interobserver agreement. The limitations of liver biopsy highlight the importance of developing new imaging biomarkers that allow accurate and non-invasive assessment of autoimmune hepatitis in terms of liver inflammation and fibrosis, developing the virtual biopsy concept. Therefore, we review the state-of-the-art of Magnetic Resonance Imaging sequences for the noninvasive evaluation of autoimmune hepatitis, including historical advances and future directions.